Low cost and comprehensive pork detection in processed food products with a different food matrix - Fenny Aulia Sugiana; Henni Widyowati; Muhammad Ali Warisman; Suryani Suryani; Desriani Desriani (Indonesian Journal of Biotechnology, 2018)
The adulteration of processed beef-based meat products with pork is a sensitive issue in Indonesia. In this study, we developed a detection method for the low cost identification of pork in processed meat products. We used the cost-efficient Taq DNA polymerase, DreamTaq Green PCR master mix (2x), and duplex PCR method to recognize pork simultaneously with 18S rRNA detection. A positive control containing a pork gene inserted into pGEM®-T easy was prepared, along with a negative control. The results of the duplex PCR were used to assess its specificity, detection limit, and its ability to recognize pork in processed meat products with a different food matrix. 18S rRNA detection was for confirming DNA integrity of DNA extracted from the processed food, while the positive control confirmed that the reagents were working well and the negative control confirmed a non-contamination problem. Following this, the duplex PCR was optimized and the optimum concentration primer for duplex PCR detection was found to be 3 µm for pork and 0.2 µm for 18S rRNA. As little as 3.125 ng of the DNA template could be used to detect whether a sample contained pork. Duplex PCR is a simple, fast, sensitive, specific, and low cost method of detecting pork in processed meat products.